2021
DOI: 10.1177/21582440211008897
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Mother-Child Mediated Learning Strategies on Cognitive Modifiability and Psychological Resilience of Children With Learning Disabilities: A Replication of Tzuriel and Shomron’s Study (2018) With Nigerian Children

Abstract: This study determined the effects of mother-child mediated learning (MCML) strategies on the psychological resilience (PR) and cognitive modifiability (CM) of children with learning disabilities (LD) using a structural equation modeling (SEM) approach. The study utilized a sample of 60 mothers and 60 children with LD. These children were both male (63%) and female (37%) primary five level children diagnosed with LD and were sampled from inclusive primary schools in Enugu State, Nigeria. The mean age and standa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…This led to designing various activities aiming to develop the sub-processes of oral expression through training on the use and recognition of different vocabulary items, correct word formation, understanding the supra linguistic processes, and the connotation of the language to suit the speaker's needs and aims. The current study agreed with what was found by the previous studies about the efficiency of the program in the mitigation of oral expression disabilities, such as (Hafez, 2006;AbouShaaban, 2010;Abdul-Azim, 2011;Goodrich et al, 2014;Ali & Al-Anazi, 2016;Seçkin, 2021;Ugwuanyi et al, 2021).…”
Section: Posttest Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…This led to designing various activities aiming to develop the sub-processes of oral expression through training on the use and recognition of different vocabulary items, correct word formation, understanding the supra linguistic processes, and the connotation of the language to suit the speaker's needs and aims. The current study agreed with what was found by the previous studies about the efficiency of the program in the mitigation of oral expression disabilities, such as (Hafez, 2006;AbouShaaban, 2010;Abdul-Azim, 2011;Goodrich et al, 2014;Ali & Al-Anazi, 2016;Seçkin, 2021;Ugwuanyi et al, 2021).…”
Section: Posttest Resultssupporting
confidence: 92%
“…Oral language stood for the contemporary definitions of learning difficulties that focus on the aspects of linguistic defects (Seçkin, 2021). Learning Disabilities Association of Canada (2012) Cited that Learning disabilities (LD) are disorders that affect the acquisition, organization, retention, understanding, or use of verbal or nonverbal information (Ugwuanyi et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…This heterogeneity is reflected in academic patterns, strengths and weaknesses in information processing, and also as specific academic disorders in particular areas (reading and writing) (Mammarella et al, 2021). Considering the poor performance, repeated failures, negative self-concept, society's biased attitudes, and communication problems of children with learning disabilities, one of the factors that can play a significant role in their behavioral and cognitive performances is the quality of parent-child interactions in the family (Ugwuanyi et al, 2021).…”
Section: Introductionmentioning
confidence: 99%